On the relationship between various anticoagulants and robot-assisted radical prostatectomy: a single-surgeon serial analysis - Farzat, Mahmoud; Wagenlehner, Florian M.; Justus Liebig University Giessen (My University, 2024)
Prostate cancer patients often have other health conditions and take anticoagulants. It was believed that surgery under anticoagulants could worsen surgical results. This study aims to explore the safety of robot-assisted prostatectomy in anticoagulated patients, without any exclusion criteria. The study included 500 patients who underwent RARP by a single surgeon between April 2019 and August 2022. Patients were divided into two groups: Group 1, consisting of 376 men (75.2%), did not receive any anticoagulation, while Group 2, with 124 patients (24.8%), received different forms of anticoagulation. Then, the anticoagulation group was divided into 4 subgroups according to their definite anticoagulation: the aspirin 15.6%, new oral anticoagulants (NOAC) 5.4%, Vitamin K antagonist (VKA) 2%, and dual-antiplatelet therapy (DAPT) 1.8% subgroup. Postoperative complications and readmission rates were compared between the two study groups and subgroups. Patients in the combined group 2 were older and they also carried more comorbidities compared to men in group 1 (p = 0.03, p = 0.001).The study groups had similar oncological results, with 40.4% of patients having locally advanced cancers. Catheter days were longer in the anticoagulation group (4.5 vs 4 days, p = 0.001). No significant differences were observed between study groups for overall, minor, and major complications (p = 0.160, 0.100, and 0.915, respectively). In addition, readmissions were low (5.6%) and similar between the study groups (p = 0.635). Under cautious management, RARP under diverse anticoagulation regimes is safe and has comparable results to men with no medications. Further prospective studies must be conducted to confirm our findings.
Keywords: ddc:610